2004
DOI: 10.1124/mol.66.3.
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 Regulates the Insulin-Like Growth Factor I-Induced Potentiation of Zn2+-Toxicity in Primary Cortical Culture

Abstract: The pretreatment of cultured cortical neurons with neurotrophic factors markedly potentiates the cytotoxicity induced by low concentrations of Zn(2+) or excitotoxins. In the current study, we investigated the mechanism underlying the insulin-like growth factor-I (IGF-I)-induced Zn(2+) toxicity potentiation. The pretreatment of primary cortical cultures for more than 12 h with 100 ng/ml of IGF-I increased the cytotoxicity induced by 80 microM Zn(2+) by more than 2-fold. The IGF-I-enhanced cell death was blocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
269
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(285 citation statements)
references
References 48 publications
13
269
3
Order By: Relevance
“…Similarly, although there is increased apoptotic cell death in the brain of TCDD-exposed larvae (Dong et al 2002), the developing spinal cord does not show the widespread cell death as observed with pyrene exposure. Most important, although CYP1A knockdown failed to modulate TCDD toxicity (Carney et al 2004), the onset of pyrene toxicity was markedly delayed in CYP1A morphants. Most evidence suggests that TCDD toxicity is related to its poor metabolism by CYP enzymes and concomitant bioaccumulation with persistent, futile AhR activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, although there is increased apoptotic cell death in the brain of TCDD-exposed larvae (Dong et al 2002), the developing spinal cord does not show the widespread cell death as observed with pyrene exposure. Most important, although CYP1A knockdown failed to modulate TCDD toxicity (Carney et al 2004), the onset of pyrene toxicity was markedly delayed in CYP1A morphants. Most evidence suggests that TCDD toxicity is related to its poor metabolism by CYP enzymes and concomitant bioaccumulation with persistent, futile AhR activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, AhR-dependent developmental defects were CYP1A independent. A CYP1A morpholino did not alter dioxin toxicity in zebrafish embryos, implicating other AhR target genes in dioxin pathophysiology (Carney et al 2004). …”
mentioning
confidence: 99%
“…NM_001033161). The ASO lead 1a is the murine homolog (a G to A base change at position 5) of the human TRADD lead reported previously (28). Control oligonucleotides 5 (5′-GCCCAATCTCGTTAGCGA-3′) were designed with six mismatches to 4 , such that they contained ≥4 mismatches to all known mouse sequence.…”
Section: Methodsmentioning
confidence: 96%
“…From FADD, the path obtained by our present method coincides with the intrinsic and the extrinsic pathway and not the path obtained by extreme pathway analysis. The intrinsic path that leads from FADD to the target gene DFF45 through the intermediate path as obtained by the present method can be found in [47][49].…”
Section: Resultsmentioning
confidence: 95%